2006
DOI: 10.1111/j.1939-1676.2006.tb01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Controlled Physiotherapy Increases Survival Time in Dogs with Suspected Degenerative Myelopathy

Abstract: The purposes of the study reported here were to evaluate the signalment and clinical presentation in 50 dogs with degenerative myelopathy, to evaluate whether mean survival time was significantly affected by various means of physiotherapy performed in 22 dogs, and to determine whether neurologic status, anatomic localization, or age at onset had an influence on survival time in dogs that received physiotherapy. We found a significant (P < .05) breed predisposition for the German Shepherd Dog, Kuvasz, Hovawart,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
48
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 8 publications
2
48
0
4
Order By: Relevance
“…Since 1973, however, the term DM most often has been used to describe a progressive neurodegenerative disease (or diseases) with characteristic clinical signs and distinct histopathologic spinal cord lesions 1–13. Most dogs are at least 8 years old before the onset of clinical signs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1973, however, the term DM most often has been used to describe a progressive neurodegenerative disease (or diseases) with characteristic clinical signs and distinct histopathologic spinal cord lesions 1–13. Most dogs are at least 8 years old before the onset of clinical signs.…”
mentioning
confidence: 99%
“…The earlier study that identified the SOD1:c.118G>A mutation focused on 5 canine breeds: Boxer, Chesapeake Bay Retriever, German Shepherd Dog, Pembroke Welsh Corgi, and Rhodesian Ridgeback 3. Nonetheless, members of many other canine breeds have been diagnosed with DM 2,5,12,13. To provide a broader view of the potential contribution of the known SOD1 missense mutations across multiple canine breeds, we here report 35,359 genotypes at SOD1:c.118 , SOD1:c.52 , or both determined using DNA samples from members of 222 canine breeds, including 249 dogs from which spinal cord segments were obtained post mortem for histopathologic evaluation.…”
mentioning
confidence: 99%
“…This is because controlled studies to investigate the efficacy of each procedure are lacking and because the knowledge of joint and muscle biomechanics in veterinary species is limited. 8 The effects of standardized movements (passive stifle joint bending, straight limb raising, and dural stretch exercise) during physical therapy exercises for mobilization of lumbar spinal nerves and the dura mater in dogs have been studied. The therapeutic effects of electrotherapy as a method of physical therapy in dogs with osteoarthritis and rupture of the cranial cruciate ligament have been reported.…”
mentioning
confidence: 99%
“…Therefore, it is important to clarify the incidence of DM and identify other factors involved in the onset of DM. More recently, another novel DM-associated mutation was identified as c.52A>T (p.T18S) in a Bernese Mountain Dog [9], which is also known as a breed predisposed to DM [3,4]. Based on these observations, veterinarians should know that the genotyping assays for the c.118G>A mutation have application limits.…”
mentioning
confidence: 99%
“…A differential diagnosis is also difficult, because PWC is a chondrodystrophic breed and prone to Hansen type I intervertebral disc disease, which often mimics and coexists with DM. Furthermore, at present, there exists no prophylactic or curative treatment for canine DM, but intensive physiotherapy may prolong survival times of DM-affected dogs [3,4]. There is a need for the development of effective therapeutic and prophylactic strategies.…”
mentioning
confidence: 99%